Development of a design research for determining the quality indicators of potential API. 1. newly synthesized substances for primary pharmacological screening - Bevz, Nataliia; Mishchenko, Volodymyr (ScienceRise: Pharmaceutical Science, 2019)
The constant growth in the world of medicinal products of synthetic origin determines the search, directed synthesis and pharmacological studies of new biologically active substances. The establishment of the structure of the substance and the study of physical and chemical properties requires the use of a number of methods and tests that allow obtaining a substance with "pharmacopoeial quality" already at the stage of synthesis of potential API. Changes in the further conditions of synthesis, solvents for crystallization, etc. can lead to a change in the profile of impurities and their quantity, obtaining other polymorphic modifications, isomers, etc. and as a result - to a change in the pharmacological properties. To prevent this, the requirements for substances that are transferred for pharmacological screening must be unified. Objective: The purpose of the work is to summarize the information of methods of establishing the structure and physico-chemical properties of new biologically active substances, assess their compliance with pharmacopoeial quality requirements and formulate mandatory requirements for standardization of first synthesized substances for their transfer for primary pharmacological screening in the form of the structure of the primary "certificate of quality". Materials and methods. The research uses the collection and analysis of data from modern scientific literature and regulatory documents. Results. The conformity of research on the structure of the first synthesized substances to pharmacopoeial quality indicators of substances has been determined, the structure of "certificate of their quality" has been proposed, the basic principles of ensuring stable quality indicators in the synthesis of API have been highlighted. Discussion. The obligatory definition for the newly synthesized substances such indicators as melting point, solubility in solvents of different polarity (lipofilicity), elemental composition and / or molecular weight is justified. From physical and chemical methods, UV, IR, and at least PMR spectroscopy are mandatory, the use of at least one of the chromatographic methods - TLC with the use of witness substances, or LC/MS (preferred, because in addition to purity allows to estimate the quantitative content of matter and the profile of impurities) is mandatory. Conclusions. Approaches to the peculiarities of establishing the structure and studying the properties of a newly synthesized substance with the promising biological activity using physical, physico-chemical and chemical methods are generalized. The methods of establishing the BAS structure are unified, which fully characterize the structure, provide information on the purity and quantity of the compound at the initial stage of pharmacological tests. The main principles of ensuring stable quality indicators in the synthesis of potential API are highlighted